Ginkgo biloba Extract EGb 761 Improves Vestibular Compensation and Modulates Cerebral Vestibular Networks in the Rat - Lindner, Magdalena; Gosewisch, Astrid; Eilles, Eva; Branner, Christina; Krämer, Anja; Oos, Rosel; Wolf, Eckhard; Ziegler, Sibylle; Bartenstein, Peter; Brandt, Thomas; Dieterich, Marianne; Zwergal, Andreas (Frontiers in Neurology, 2019)
Unilateral inner ear damage is followed by behavioral recovery due to central vestibular compensation. The dose-dependent therapeutic effect of Ginkgo biloba extract EGb 761 on vestibular compensation was investigated by behavioral testing and serial cerebral [18F]-Fluoro-desoxyglucose ([18F]-FDG)-µPET in a rat model of unilateral labyrinthectomy (UL). Five groups of 8 animals each were treated with EGb 761-supplemented food at doses of 75, 37.5 or 18.75mg/kg body weight 6 weeks prior and 15 days post UL (groups A,B,C), control food prior and EGb 761-supplemented food (75mg/kg) for 15 days post UL (group D), or control food throughout (group E). Plasma levels of EGb 761 components bilobalide, ginkgolide A and B were analyzed prior and 15 days post UL. Behavioral testing included clinical scoring of nystagmus, postural imbalance, head roll tilt, body rotation during sensory perturbation and instrumental registration of locomotion and spatial orientation in an open field before and 1,2,3,5,7,15 days after UL. Whole-brain [18F]-FDG-µPET was recorded before and 1,3,7,15 days after UL. The EGb 761 group A (75mg/kg prior and post UL) showed a significant reduction of nystagmus scores (1,2,3,5 days post UL), of postural asymmetry (1,3,5,7 days post UL), and an increase in locomotion velocity (5 and 7 days post UL) as compared to controls (group E). Application of EGb 761 at doses of 37.5 and 18.75mg/kg prior and post UL (groups B,C) and EGb 761 at a dose of 75mg/kg post UL (group D) resulted in faster recovery of nystagmus and postural asymmetry, but did not influence gait speed relative to controls. Locomotor velocity increased with higher plasma levels of ginkgolide A and B. Serial [18F]-FDG-µPET revealed a significant increase of the regional cerebral glucose metabolism in the hippocampal formation and a decrease in the cerebellum in the EGb 761 group A (75mg/kg prior and post UL) versus control on days 1 and 3 after UL. In conclusion, Ginkgo biloba extract EGb 761 improves vestibulo-ocular motor, vestibulo-spinal and locomotor compensation after UL significantly and dose-dependently. This rat study supports the translational approach of using EGb 761 at higher dosages for medical acceleration of vestibular compensation in acute vestibular loss.